Polygamy in Northern Malawi: A Christian Reassessment - Mlenga, Moses (Mzuni Press, 2016)
Cover -- Copyright page -- Title page -- Dedication -- Acknowledgements -- Contents -- Abbreviations -- Introduction -- Chapter 1 - From Livingstonia Mission to the Synod of Livingstonia -- Chapter 2 - Polygamy in the Missiological Discourse -- Chapter 3 - Polygamy in Biblical Times: An Overview -- Chapter 4 - Polygamy in the Traditional Societies of Northern Malawi -- Chapter 5 - Forms of Polygamy -- Chapter 6 - Polygamy as a Feminist Challenge -- Chapter 7 - A Pastoral Theology for Polygamous Members -- Chapter 8 - Road Map for Acceptance of Polygamists as Full Coomunicant Members